Zgodovina uporabe konoplje in kanabinoidov - Kočevar Glavač, Nina (Farmacevtski vestnik, 2016)
Since the first beginnings some 5000 years ago, with the rise in the late 19th century, with the decline in the early 20th century, and with the renewed rise in the 21st century, cannabis belongs to one of the most interesting (medicinal) plants, which has justified the interest of science, medicine as well as industry. In the article, a short historical review of cannabis and cannabinoids medicinal use is presented. Some other areas, botany and broader historical circumstances, are mentioned in order to allow broader understanding as well as a critical and objective view of their future medicinal use.
Keywords: Cannabis; kanabinoidi; Konoplja; medicinska uporaba